Assessing the effect of K2CO3 and aqueous phase recycling on hydrothermal liquefaction of corn stover. (June 2022) - Carpio, Rowena B.; Avendaño, Chris Ian L.; Basbas, Carlo A.; Habulan, Aljay A.; Guerrero, Gino Apollo M.; Maguyon-Detras, Monet Concepcion; Bambase, Manolito E.
Abstract: The effects of reaction temperature (300–340 °C) and reaction time (30–90 min), catalyst loading (0–10% K2 CO3 ), and aqueous phase recycling (up to 3 recycling rounds) on the hydrothermal liquefaction (HTL) of corn stover were investigated. The oil yield ranged from 0.28 to 14.54%daf. A high reaction temperature and a long reaction time have a synergistic effect on the oil production under non-catalytic HTL. The effect of K2 CO3 loading on oil yield is dependent on the reaction temperature. The FTIR analysis of the solid residue showed that the peak characteristics of lignin and cellulose are still intact without or with different K2 CO3 loading suggesting low lignin and cellulose degradation. The effect of the aqueous phase with the presence of K2 CO3 showed an increased oil yield, energy recovery, and abundance in silanes and siloxanes after the 3rd round of recycling. Graphical abstract: Unlabelled Image Highlights: Oil yield from corn stover with K2 CO3 depends on reaction temperature. A proper amount of K2 CO3 can improve oil production from corn stover. Oils produced are rich in silanes and siloxanes. Oil yield, ER, and Si-containing compounds in oil increased after 3rd recycling.